2022
DOI: 10.3389/fimmu.2022.996348
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictive value of naïve and memory T cells in advanced NSCLC

Abstract: Currently, there is no sensitive prognostic biomarker to screen out benefit patients from the non-benefit population in advanced non-small cell lung cancer patients (aNSCLCs). The 435 aNSCLCs and 278 normal controls (NCs) were recruited. The percentages and absolute counts (AC) of circulating naïve and memory T lymphocytes of CD4+ and CD8+ T cells (Tn/Tm) were measured by flow cytometry. The percentage of CD4+ naïve T (Tn), CD8+ Tn, CD8+ T memory stem cell (Tscm), and CD8+ terminal effector T cell decreased ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…24 These cells, which are specific for many viral and self-tumor antigens, were identified in a subpopulation of T cells known as naive T cells, which had the following characteristics: CD27 + , CD45RO − , CCR7 + , CD45RA + , CD62L + , CD28 + , and IL-7R + . It has been revealed that high TSCM infiltration was associated with good prognosis in advanced NSCLC patients receiving anti-PD-1 immunotherapy, 25 indicating the significant prognostic value of TSCM in human cancer. However, their role in CRC remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…24 These cells, which are specific for many viral and self-tumor antigens, were identified in a subpopulation of T cells known as naive T cells, which had the following characteristics: CD27 + , CD45RO − , CCR7 + , CD45RA + , CD62L + , CD28 + , and IL-7R + . It has been revealed that high TSCM infiltration was associated with good prognosis in advanced NSCLC patients receiving anti-PD-1 immunotherapy, 25 indicating the significant prognostic value of TSCM in human cancer. However, their role in CRC remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The representative clinicopathology images, obtained from the TCGA data, shown for each of the three cluster subtypes in Figure S3 B, revealed that immune cell infiltration was higher in the tumor nests of cluster B patients than in the other two clusters. Increased CD4 + and CD8 + T cell infiltration has previously been reported to be correlated with better prognosis [ 30 , 31 ], which may explain why cluster B had the longest OS among the three clusters. GSVA exhibited inter-cluster distinction in the functional enrichment pathways (Figure S3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical and preclinical studies indicate that memory cells could be more important in cancer curative immunity [57]. A recently published study showed that an insufficient number of central memory T cells in NSCLC cannot induce an adequate antitumor immune response and kill tumor cells, which may partially explain the development of refractory tumors [58].…”
Section: Discussionmentioning
confidence: 99%